Well-posedness and exponential stability for coupled Lamé system with viscoelastic term and strong damping. (15th June 2018) - Beniani, Abderrahmane; Taouaf, Noureddine; Benaissa, Abbes
Abstract: In this paper, we consider a coupled Lamé system with a viscoelastic term and a strong damping. We prove well posedness by using Faedo–Galerkin method and establish an exponential decay result by introducing a suitable Lyapunov functional.